Comparative genomic analyses illuminate the distinct evolution of megabats within Chiroptera. (23rd September 2020) - Nikaido, Masato; Kondo, Shinji; Zhang, Zicong; Wu, Jiaqi; Nishihara, Hidenori; Niimura, Yoshihito; Suzuki, Shunta; Touhara, Kazushige; Suzuki, Yutaka; Noguchi, Hideki; Minakuchi, Yohei; Toyoda, Atsushi; et al.
Abstract: The revision of the sub-order Microchiroptera is one of the most intriguing outcomes in recent mammalian molecular phylogeny. The unexpected sister–taxon relationship between rhinolophoid microbats and megabats, with the exclusion of other microbats, suggests that megabats arose in a relatively short period of time from a microbat-like ancestor. In order to understand the genetic mechanism underlying adaptive evolution in megabats, we determined the whole-genome sequences of two rousette megabats, Leschenault's rousette ( Rousettus leschenaultia ) and the Egyptian fruit bat ( R. aegyptiacus ). The sequences were compared with those of 22 other mammals, including nine bats, available in the database. We identified that megabat genomes are distinct in that they have extremely low activity of SINE retrotranspositions, expansion of two chemosensory gene families, including the trace amine receptor ( TAAR ) and olfactory receptor ( OR ), and elevation of the dN / dS ratio in genes for immunity and protein catabolism. The adaptive signatures discovered in the genomes of megabats may provide crucial insight into their distinct evolution, including key processes such as virus resistance, loss of echolocation, and frugivorous feeding.